The Tourism Area Life Cycle of Borobudur Temple in the Colonial Era - Arianto, Ego Vinda A.P.Y.; Herwandi, Herwandi; Asnan, Gusti (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The utilisation of Borobudur Temple as a tourist destination commenced during the colonial period. This article seeks to examine the life cycle of Borobudur Temple as a tourist destination during the colonial times. This research employs the historical method through four stages: heuristics, source criticism, interpretation, and historiography. Using the Tourism Area Life Cycle (TALC) model, the article shows that the life cycle of Borobudur Temple as a tourist destination unfolded in three stages: exploration, involvement, and development. The exploration stage is thought to have occurred between the 1830s and 1870s, characterized by the lack of special facilities for tourists. The involvement stage is dated to have occurred between the 1870s and 1911, distinguished by the active involvement of the local community in the provision of tourism services, particularly in the areas of accommodation and transportation. The final stage (development), spanning from 1911 to 1942, saw the emergence of mass tourism at Borobudur Temple. This phenomenon can be attributed to the intensifying efforts of tourism promotion by various institutions.